2014
DOI: 10.1089/pop.2013.0017
|View full text |Cite
|
Sign up to set email alerts
|

Results of the Promoting Effective Advance Care Planning for Elders (PEACE) Randomized Pilot Study

Abstract: The specific aim of the PEACE pilot study was to determine the feasibility of a fully powered study to test the effectiveness of an in-home geriatrics/palliative care interdisciplinary care management intervention for improving measures of utilization, quality of care, and quality of life in enrollees of Ohio's community-based long-term care Medicaid waiver program, PASSPORT. This was a randomized pilot study (n=40 intervention [IG], n=40 usual care) involving new enrollees into PASSPORT who were >60 years old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
71
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(71 citation statements)
references
References 17 publications
0
71
0
Order By: Relevance
“…Quality of life was assessed in 24 studies (55.8%) (4576 patients), of those 12 9,10,20,32,35,44,48,5155 were at high risk; 5, 11,13,31,42,56 unclear risk; and 7, 8,12,33,5760 low risk of bias. Sixteen trials (67%) exclusively comprised patients with cancer.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Quality of life was assessed in 24 studies (55.8%) (4576 patients), of those 12 9,10,20,32,35,44,48,5155 were at high risk; 5, 11,13,31,42,56 unclear risk; and 7, 8,12,33,5760 low risk of bias. Sixteen trials (67%) exclusively comprised patients with cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 29 trials involving 10105 patients and assessing physical symptoms, 17 had a high risk of bias, 9,10,20,4345,47–49,51,52,54,55,6164 5 had an unclear risk of bias, 37,42,46,50,65 and 7 had a low risk 8,12,33,5760 of bias. Ten trials reported statistically significant reductions in specific physical symptoms or a composite symptom indicator.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations